2021
DOI: 10.1016/j.dcn.2021.100969
|View full text |Cite
|
Sign up to set email alerts
|

The development of theta and alpha neural oscillations from ages 3 to 24 years

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
160
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(205 citation statements)
references
References 131 publications
(205 reference statements)
41
160
4
Order By: Relevance
“…These findings were present both when using the signal averaged across the entire scalp, and when using electrode clusters covering anterior, central, and posterior regions separately (Figure 2B and 2C), thus suggesting that systematic variations with age are a relatively widespread phenomenon. Importantly, our findings also replicate recent observations of flattening of the aperiodic exponent with age in infancy , as well as in cohorts with ages ranging from childhood into adulthood (Cellier et al, 2021;Donoghue et al, 2020a;He et al, 2019;Tröndle et al, 2020). The present results, in conjunction with previous findings, are therefore supportive of quantitative neurodevelopmental changes in the aperiodic component of the EEG signal.…”
Section: Age Predicts Aperiodic Properties Of the Eeg Signalsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings were present both when using the signal averaged across the entire scalp, and when using electrode clusters covering anterior, central, and posterior regions separately (Figure 2B and 2C), thus suggesting that systematic variations with age are a relatively widespread phenomenon. Importantly, our findings also replicate recent observations of flattening of the aperiodic exponent with age in infancy , as well as in cohorts with ages ranging from childhood into adulthood (Cellier et al, 2021;Donoghue et al, 2020a;He et al, 2019;Tröndle et al, 2020). The present results, in conjunction with previous findings, are therefore supportive of quantitative neurodevelopmental changes in the aperiodic component of the EEG signal.…”
Section: Age Predicts Aperiodic Properties Of the Eeg Signalsupporting
confidence: 92%
“…A further study containing EEG recordings from both children and young adults (age range 5-21 years), the majority (~ 88%) of whom had a psychiatric diagnosis, also reported a flattening of the aperiodic exponent, and reduction in offset with increasing age (Tröndle et al, 2020). Similarly, Cellier et al (2021) recently reported a similar trend in a sample containing both children and adults (age range 3-24 years).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations